Carvedilol attenuates carbon tetrachloride-induced liver fibrosis and hepatic sinusoidal capillarization in mice - Wu Y; Li Z; Xiu AY; Meng DX; Wang SN; Zhang CQ (Dove Medical Press, 2019)
Ying Wu,1 Zhen Li,2 Ai-Yuan Xiu,1 Dong-Xiao Meng,1 Si-Ning Wang,1 Chun-Qing Zhang11Department of Gastroenterology, Shandong Provincial Hospital Affiliated to Shandong University, Jinan, Shandong Province, People’s Republic of China; 2Department of Health Digestion, Shandong Provincial Hospital Affiliated to Shandong University, Jinan, Shandong Province, People’s Republic of ChinaAim: To investigate the effect of carvedilol on liver fibrosis and hepatic sinusoidal capillarization in mice with carbon tetrachloride (CCl4)-induced fibrosis.Methods: A liver fibrosis mouse model was induced by intraperitoneal CCl4 injection for 8 weeks. The mice were divided into five experimental groups: the normal group, the oil group, the CCl4 group, the CCl4+carvedilol (5 mg/kg/d) group, and the CCl4+carvedilol (10 mg/kg/d) group. The extent of liver fibrosis was evaluated by histopathological staining, and the changes in fenestrations of hepatic sinus endothelial cells were observed by scanning electron microscope (SEM). The expression of α-smooth muscle actin (α-SMA) and vascular endothelial markers was detected by immunohistochemistry and Western blot assays. The effect of carvedilol on cell apoptosis was studied via Terminal deoxynucleotidyl Transferase Mediated dUTP Nick End Labeling (TUNEL) assay, and the serum levels of matrix metalloproteinase-8 (MMP-8), vascular endothelial growth factor (VEGF), and angiopoietin-2 were detected through a Luminex assay.Results: Liver fibrosis in CCl4-treated mice was attenuated by reduced accumulation of collagen and the reaction of inflammation with carvedilol treatment. Carvedilol reduced the activation of hepatic stellate cells (HSCs) and increased the number of apoptotic cells. The expression of α-SMA, CD31, CD34 and VWF (von Willebrand factor) was significantly decreased after carvedilol treatment. In addition, the number of fenestrae in the hepatic sinusoid showed notable differences between the groups, and the serum levels of MMP-8, VEGF and angiopoietin-2 were increased in the mice with liver fibrosis and reduced by carvedilol treatment.Conclusion: The study demonstrated that carvedilol could prevent further development of liver fibrosis and hepatic sinusoidal capillarization in mice with CCl4-induced fibrosis.Keywords: carvedilol, liver fibrosis, hepatic sinusoid, angiogenesis, hepatic stellate cell, mice